Increasing Student Activity in PAI Learning at SDN 18 Class IV In Pandahan River - Sri Diana (BiCED Proceeding, 2024)
This study aims to determine the impact of implementing the Project-Based Learning (PJBL) model on enhancing students' understanding and engagement in the topic of Belief in the Messengers of Allah in grade IV at SD Negeri 18 Sungai Pandahan, Lubuk Sikaping. This research uses a classroom action research (CAR) approach with two cycles. In the first cycle, the application of the Problem-Based Learning (PBL) model showed improvement despite challenges in student motivation and understanding of the model. The second cycle employed the PJBL model, which was more effective as students were directly involved in learning projects that encouraged creativity and collaboration. The test results and observations showed that after applying PJBL, 90.48% of students passed the test, and student activity increased with 71.43% in the excellent category. These findings indicate that PJBL significantly enhances both students' understanding of the material and their active participation.